KEPATUHAN PAJAK DALAM PERSPEKTIF EKONOMI PERILAKU: PENGARUH ALTRUISME DAN STATUS MELALUI EKSPERIMEN LABORATORIUM - Sustiyo, Joko; Putri Permatasila (Polytechnic of State Finance STAN, 2025)
Tax compliance remains a crucial issue for developing countries, partly because tax revenue ratios are still far behind the global average in Indonesia. While economic factors affecting tax compliance have been widely studied, the influence of non-economic factors, particularly altruism and status, has been rarely explored in the Indonesian context. This study examines the influence of altruism and its status on tax compliance behaviour using a laboratory experiment involving 42 participants, including tax officials, non-tax civil servants, and students. The experiment was designed in five stages that simulated real financial decision-making and applied self-assessment and random audit mechanisms. Altruism was operationalised through voluntary donation opportunities, while status was categorised based on professional background. Data analysis used two-way ANOVA and binary logistic regression to assess the influence and interaction of independent variables on tax compliance. The results showed that both altruism and status significantly influenced tax compliance. Interestingly, individuals with altruistic tendencies are less likely to comply with tax obligations, suggesting a possible substitution effect between voluntary giving and tax obligations. Tax employees also demonstrated higher compliance levels than non-tax employees and students. No significant interaction between altruism and status was found. The results emphasise the important role of behavioural factors in formulating tax policies. This study also contributes to the limited literature on experimental tax compliance in Indonesia and provides empirical evidence to support tax policies.